Nature’s Power: Integrating STEAM in Outdoor Learning to Unlocking Enhance 4C Skills and Science Pedagogical Knowledge - Jupriyanto, Jupriyanto; Sari, Yunita; Hidayah, Ratna; Salimi, Moh (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
Outdoor learning, as a form of science pedagogical knowledge, plays a vital role in equipping elementary learners with 21st-century competencies. This qualitative case study explores how outdoor learning at SD Alam Ungaran, a nature-based Islamic elementary school in Indonesia, can foster the development of critical thinking, creativity, communication, and collaboration (4C) skills grounded in a STEAM-integrated thematic curriculum. This study collected data through document analysis, semi-structured interviews, and direct classroom observations. Data was analyzed by emphasizing coding, condensation, and thematic interpretation via NVivo 12 Pro. Findings revealed that outdoor learning significantly enhances 4C skills through experiential and project-based activities embedded in real-world environmental contexts. Students’ critical thinking skill is nurtured through inquiry and direct observation, while the creativity is stimulated through innovative ecological projects. Students developed their communication skills via interactive group discussions and presentations, and reinforced their collaboration skills through cooperative tasks such as market day and eco-projects. Moreover, students enriched their pedagogical science knowledge through the integration of STEAM concepts in authentic field activities. The SD Alam Ungaran integrated STEAM concepts and environmental ethics uniquely further to support the development of students’ holistic moral, emotional, and social skills. The implications of these results can be a best practice for schools to create an integrative curriculum that supports the development of 21st-century skills.